2010
DOI: 10.1246/bcsj.20100032
|View full text |Cite
|
Sign up to set email alerts
|

Consideration on the Metachromatic Spectra of Toluidine Blue Dimers Formed on DNA Oligomers

Abstract: Metachromatic staining with toluidine blue (TB) has been used as a cytological tool for tissue recognition and cancer diagnosis. Recently, its strong potential for infertility diagnosis was also reported. Metachromatic staining is important in biological applications, but the origin of spectral changes has not been fully understood, although dye aggregation on biological materials is thought to be the cause. In this study, we investigated the dimer structure of TB formed on DNA oligomers by using a computation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
6
0
4
Order By: Relevance
“…The ability to bind cationic dimethyl-amino residues of the aromatic stain toluidine blue by two neighbour phosphate residues of the DNA backbone in the A-form helix was found improbable due to its too narrow minor groove [ 40 ]. However, Dearing et al [ 41 ] found that acridines prefer a mixed intercalation mechanism using both minor and major grooves, while the analysis by Sinha et al [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to bind cationic dimethyl-amino residues of the aromatic stain toluidine blue by two neighbour phosphate residues of the DNA backbone in the A-form helix was found improbable due to its too narrow minor groove [ 40 ]. However, Dearing et al [ 41 ] found that acridines prefer a mixed intercalation mechanism using both minor and major grooves, while the analysis by Sinha et al [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In such conditions, the toluidine blue (TB), a conventional indicator in colloidal titration [53], was investigated to directly quantify siRNA in various solvent conditions [54][55][56]. The TB is a positively charged dye that can interact with phosphate groups of siRNA through electrostatic interaction [57]. A depletion approach was used in which the dispersions of complexes were first incubated with an excess of TB.…”
Section: Complexation Of Cos With Sirnamentioning
confidence: 99%
“…Metachromasia may be used in the identification of active mast cells in the early stages of pancreatitis (Lopez-Font et al, 2010). Metachromatic staining is very important in biological applications, such as tissue recognition (Sato et al, 2010). Metachromasia is reduced in case of granule swelling and active degranulation in mast cells (Nielsen et al, 1981).…”
Section: Introductionmentioning
confidence: 99%